STUDI LITERATUR ANALISIS PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DENGAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK - Syahti Runia Hidayah; Nurhasanah Siregar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
The purpose of this study is to describe the results of the analysis of improving students' mathematical communication skills with Realistic Mathematics Education approach. The type of this research is descriptive qualitative research using the library research method. The subject of this research is the most published articles in published journals about mathematical communication skills through Realistic Mathematics Education approach to junior high school students. Based on the findings from 5 journals, it was found that students' mathematical communication improved better in students who studied with Realistic Mathematics Education approach compared to students who studied with conventional learning. Realistic Mathematics Education approach can improve students' ability to describe, understand, and represent mathematical ideas contained in pictures, tables or diagrams. So, Realistic Mathematics Education approach is one approach that can improve students' mathematical communication skills at the junior high school level with effect size score of 1,158 in the large effect category.